An overview of preclinical models of traumatic brain injury (TBI): relevance to pathophysiological mechanisms - Fesharaki-Zadeh, Arman; Datta, Dibyadeep (Frontiers in Cellular Neuroscience, 2024)
Traumatic brain injury (TBI) is a major cause of morbidity and mortality, affecting millions annually worldwide. Although the majority of TBI patients return to premorbid baseline, a subset of patient can develop persistent and often debilitating neurocognitive and behavioral changes. The etiology of TBI within the clinical setting is inherently heterogenous, ranging from sport related injuries, fall related injuries and motor vehicle accidents in the civilian setting, to blast injuries in the military setting. Animal models of TBI, offer the distinct advantage of controlling for injury modality, duration and severity. Furthermore, preclinical models of TBI have provided the necessary temporal opportunity to study the chronic neuropathological sequelae of TBI, including neurodegenerative sequelae such as tauopathy and neuroinflammation within the finite experimental timeline. Despite the high prevalence of TBI, there are currently no disease modifying regimen for TBI, and the current clinical treatments remain largely symptom based. The preclinical models have provided the necessary biological substrate to examine the disease modifying effect of various pharmacological agents and have imperative translational value. The current review will include a comprehensive survey of wellestablished preclinical models, including classic preclinical models including weight drop, blast injury, fluid percussion injury, controlled cortical impact injury, as well as more novel injury models including closed-head impact model of engineered rotational acceleration (CHIMERA) models and closed-head projectile concussive impact model (PCI). In addition to rodent preclinical models, the review will include an overview of other species including large animal models and drosophila. There are major neuropathological perturbations post TBI captured in various preclinical models, which include neuroinflammation, calcium dysregulation, tauopathy, mitochondrial dysfunction and oxidative stress, axonopathy, as well as glymphatic system disruption. The preclinical models of TBI continue to offer valuable translational insight, as well as essential neurobiological basis to examine specific disease modifying therapeutic regimen.